Edukasi Lingkungan: Program Kerja Pembuatan Papan Penjelasan Lama Terurai Sampah - Aji Purnama; Defri Wijaya; Asrul Remadan; Prima Ramadhania; Yoga Yoga; Methatias Ayu Moulina; Fadlul Amdhi Yul; Mujiono Mujiono (Jurnal Dehasen Mengabdi, 2026)
Community Service Program (KKN) is a form of community service that aims to provide solutions to social problems in the surrounding environment. One of the problems identified is the lack of public awareness about the impact of non-biodegradable waste on the ecosystem, through a visual and interactive approach. The implementation method includes collecting scientific data on the decomposition time of waste such as plastic (hundreds to thousands of years), paper (2-6 months), and organic materials (several weeks), followed by the design of informative and engaging educational boards. The boards are designed for use in schools, communities, and public spaces, with graphic elements, facts, and waste reduction tips. The program results show an increase in participants' understanding of the importance of recycling and waste management, as well as the potential for reducing waste production by up to 20% in the implementation area. In conclusion, this program not only educates but also encourages concrete actions for environmental sustainability, with recommendations for expansion to the national level